An Ortho‐Tetraphenylene‐Based "Geländer" Architecture Consisting Exclusively of 52 sp2‐Hybridized C Atoms. Issue 52 (5th August 2021) - Dekkiche, Hervé; Malinčik, Juraj; Prescimone, Alessandro; Häussinger, Daniel; Mayor, Marcel
Abstract: A new type of "Geländer" molecule based on a ortho ‐tetraphenylene core is presented. The central para ‐quaterphenyl backbone is wrapped by a 4, 4'‐di(( Z )‐styryl)‐1, 1'‐biphenyl banister, with its aryl rings covalently attached to all four phenyl rings of the backbone. The resulting helical chiral bicyclic architecture consists exclusively of sp 2 ‐hybridized carbon atoms. The target structure was assembled by expanding the central ortho ‐tetraphenylene subunit with the required additional phenyl rings followed by a twofold macrocyclization. The first macrocyclization attempts based on a twofold McMurry coupling were successful but low yielding; the second strategy, profiting from olefin metathesis, provided satisfying yields. Hydrogenation of the olefins resulted in a saturated derivative of similar topology, thereby allowing the interdependence between saturation and physico‐chemical properties to be studied. The target structures, including their solid‐state structures, were fully characterized. The helical chiral bicycle was synthesized as a racemate and separated into pure enantiomers by HPLC on a chiral stationary phase. Comparison of recorded and simulated chiroptical properties allowed the enantiomers to be assigned. Abstract : Circles in a spiral : The synthesis and physical properties of a helical chiral bicyclic hydrocarbon are presented. The design of the Geländer architecture is based on a rigid, chiral, room‐temperature‐stable central ortho ‐tetraphenylene subunit, which is further developed and twice macrocyclized to provide the target structure. Pure enantiomers are obtained by chromatography with a chiral stationary phase and allow the investigation of the chiroptical properties. Comparison between recorded and simulated CD spectra allows these enantiostable model compounds to be assigned.